Copernicus Sentinel–3B – GPS L2C tracking tests during commissioning phase. Issue 2 (15th July 2021) - Berzosa-Molina, Javier; Peter, Heike; Fernández, Jaime; Féménias, Pierre
Abstract: The Copernicus Sentinel–3B, the twin satellite of Copernicus Sentinel–3A, was launched on 25 April 2018. During its commissioning phase, the radar altimeter satellite has been flying in tandem with Sentinel–3A, only 30 s apart. This was mainly done for calibration and validation of the instruments on-board Sentinel–3B, maximizing the correlation of measurements taken by both Sentinel–3 satellites. The commissioning phase of Sentinel–3B and thus the tandem flight with Sentinel–3A has also been used to do several tests with the RUAG GPS receivers on-board Sentinel–3B. Future missions like the Copernicus Sentinel–C and –D satellites and the Copernicus Sentinel–6 (Jason-CS) satellite will carry an enhanced RUAG GNSS receiver (PODRIX). The GPS receivers on Sentinel–3B already have the capability to track the GPS L2C signal, which will become important for the future when the number of GPS satellites transmitting the L2C signal increase from currently 19 satellites up to the full GPS constellation. To test the receiver's L2C tracking performance, the redundant receiver on Sentinel–3B has been running in parallel to the main receiver with L2C tracking enabled, either exclusively or in a mixed P(Y)&L2C configuration. The performance of this new signal is analysed in detail. The Sentinel–3B POD processing chain running at the Copernicus POD Service is used to determine orbits based on the P(Y) signals from the main receiver and based on C/A plus the new L2C signal from the redundant receiver, all of them publicly available via the Copernicus Open Access Hub. The Sentinel–3B POD performance is compared to that of Sentinel–3A and the results of the Sentinel–3B redundant receiver are directly compared to the results of the main receiver. Results are compared in terms of observation metrics, estimated orbit parameters and differences to internal and external orbit products. External orbit validation is done with Satellite Laser Ranging (SLR) measurements to the satellites. Although only 19 GPS satellites are currently broadcasting the L2C signal, the resulting orbits are of equivalent quality as the operational orbit products based on P(Y) data from the full GPS constellation. SLR mean and standard deviation of 0.37 ± 1.32 cm and 0.39 ± 1.43 cm for the main and redundant receiver solutions, respectively, confirm the orbit accuracy independent of the signals used for POD. The percentage of more than five observations per epoch is still very low with approx. 15% considering the current L2C capable GPS constellation. Increase of this percentage is analysed based on a step-wise increase of the L2C capable GPS satellites up to a GPS constellation of 31 satellites.